Keragaman Sifat Kualitatif Dan Kuantitatif Kambing Jawarandu Betina Pada Peternakan Rakyat Dan Industri Di Kalimantan Timur - Surya Nur Rahmatullah; Rawa Swuandana; A Sulaiman (Universitas Islam Kadiri, 2022)
The ewe Jawarandu goat is one type of livestock that is currently developing both on smallholder farms and industrial-scale farms. The effect of the application of management on goats productivity is reflected in the quality of the qualitative and quantitative traits that develop in goats. This study aims to determine the qualitative and quantitative characteristics of ewe Jawarandu goats in smallholder farms and livestock industries in East Kalimantan. This research was conducted in two places, namely community farms in Lempake Village, Samarinda Utara District, and at PT. Equalindo Farm, Tenggarong Seberang, East Kalimantan. The study used a purposive sampling method, namely the collection technique according to the criteria determined by the researcher, with goats aged 6-24 months. Sampling data using total sampling with all the population according to the criteria as a sample. The results of study stated that the ewe Jawarandu goats in East Kalimantan were dominated by white-brown goats. The results of quantitative characteristics show that average body size in smallholder farms is sequentially higher at body length 57.81±7.35, chest circumference 63.5±6.62, shoulder height 61.31±5.96, and body weight 23. ,65±7.35, while on an industrial scale, the average value was lower with successively at body length 52.54±3.83, chest circumference 60.72±4.28, shoulder height 56.18±5.79 and body weight 19.53±3.42. Several factors that can affect the qualitative and quantitative differences in goats in two different managements are related to the application of management, especially livestock selection, and factors adaptation to the environment. The relationship between selection and adaptation affects goat's productivity.